Turning mental health into social action - Guerin, Bernard, 1957- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
This book offers a refreshing new approach to mental health by showing how mental health' behaviours, lived experiences, and our interventions arise from our social worlds and not from our neurophysiology gone wrong. It is part of a trilogy which offers a new way of doing psychology focusing on people's social and societal environments as determining their behaviour, rather than internal and individualistic attributions. Mental health' behaviours are carefully analysed as ordinary behaviours which have become exaggerated and chronic because of the bad life situations people are forced to endure, especially as children. This shifts mental health treatments away from the dominance of psychology and psychiatry to show that social action is needed because many of these bad life situations are produced by our modern society itself. By providing new ways for readers to rethink everything they thought they knew about mental health issues and how to change them, Bernard Guerin also explores how by changing our environmental contexts (our local, societal, and discursive worlds), we can improve mental health interventions. This book reframes mental health' into a much wider social context to show how societal structures restrict our opportunities and pathways to produce bad life situations, and how we can also learn from those who manage to deal with the very same bad life situations through crime, bullying, exploitation, and dropping out of mainstream society, rather than through the mental health' behaviours. By merging psychology and psychiatry into the social sciences, Guerin seeks to better understand how humans operate in their social, cultural, economic, patriarchal, discursive, and societal worlds, rather than being isolated inside their heads with a faulty brain', and this will provide fascinating reading for academics and students in psychology and the social sciences, and forcounsellors and therapists.
OCLC-licensed vendor bibliographic record.
Keywords: Psychology -- Social aspects; Mental health -- Social aspects; PSYCHOLOGY / General; PSYCHOLOGY / Applied Psychology; PSYCHOLOGY / Social Psychology